IgA-nephropathy associated with axial spondyloarthritis that debuted in adolescence: a case report. - Menkus, Olena; Grishyna, Olena (Annals of Mechnikov’s Institute, 2023)
Introduction. IgA nephropathy is the most common form of glomerulonephritis that associated with the presence of mesangial deposits of IgA. This nephropathy may be associated with other diseases: Henoch-Schonlein purpura, hepatitis, Crohn’s disease, celiac disease, psoriasis, HIV infection, spondyloarthritis, rheumatoid arthritis, Reiter’s syndrome, Behcet’s disease, scleritis, and uveitis. Case report. A case of a 29-year-old man diagnosed with axial SpA and IgA-nephropaty is reported. The patient first developed pain in the joints at the age of 13, achillitis was found a year later. At the age of 15 a symptoms of kidney damage were developed; a diagnosis of interstitial nephritis was established (clinically). Two years later the patient was hospitalized in the rheumatology department where the diagnosis of ankylosing spondylitis was established, it was confirmed by MRI. At the age of 26 in the nephrology department diagnosed with "Chronic kidney disease (CKD) Stage 2, Chronic glomerulonephritis". No pathogenetic therapy for CKD during all this time was administred, a nephrobiopsy was not performed. When contacting a rheumatologist in 2020: BASDAI (Bath ankylosing spondylitis disease activity index) - 7,0, BASFI (Bath Ankylosing Spondylitis Functional Index) – 7,7. Laboratory abnormalities: HLA B27 positive, Hematology: Hemoglobin 118 g/l (ranges 127 g/l -181 g/l), RBC 3.9 × 10 12/L (ranges 4.5 × 10 12/L - 6.4 ×10 12/L), Chemistry: C-reactive protein 1.59 mg/l, GRF (MDRD) - 52.297 ml/min/1.73 m2. Uinalysis: protein + 1, blood + 2, erythrocytes - 41 in the field (ranges 0 in the field - 3 in the field). 2011 to 2018 the patient received sulfasalazine as disease modifying therapy, then the drug was discontinued and the patient switched to rheumoxicam at a dose of 7.5 mg. However, rheumoxicam was discontinued by a nephrologist and the patient started treatment with a tumor necrosis factor-alpha inhibitor. One year later on examination: BASDAI 2.8, BASFI 1,2. Laboratory abnormalities: Hematology: Hemoglobin 123 g/l (ranges 127 g/l - 181 g/l), RBC 4.1 × 10 12/L (ranges 4.5 × 10 12/L - 6.4 × 10 12/L), Chemistry: C-reactive protein 1.2 mg/l, GRF (MDRD) - 36.573 ml/min/1.73 m2. Uinalysis: protein + 1, blood + 3, erythrocytes - 38 in the field (ranges 0 in the field – 3 in the field). Thus, the patient’s SpA symptoms improve and the GRF continues to decrease. The patient agreed to a kidney biopsy and a pathomorphological diagnosis was: pathomorphological, histochemical, immunohistochemical data indicate IgA nephropathy with a pronounced tubulo-interstitial component, a large number of positive B-lymphocytes in cells infiltrates. MEST-score -M1, E1, S1, T1, G2 - JgA-nephropathy Oxford classification 2009, 2016. Chronic stage (2017, Sethi et al) - CG3 (moderate chronic change - total renal chronic score TRCS 6 points): glomerulosclerosis (GS) 2, interstitial fibrosis (IF) 1, tubular atrophy (TA) 2, arteriosclerosis (CV) 1. Based on these results the patient was prescribed with methylprednisolone 32 mg per day, with following correction, and discontinued TNFα inhibitor. Here are the results of the examination after 5 months. BASDAI 2.8, BASFI 1,2. Laboratory abnormalities: Hematology: Hemoglobin 100 g/l (ranges 130 g/l - 160 g/l), RBC 3.21 × 10 12/L (ranges 4.0 × 10 12/L - 5.0 × 10 12/L), Chemistry: C-reactive protein 0.56 mg/l, GRF (MDRD) - 41.537 ml/min/1.73 m2. Uinalysis: protein + 1, blood + 2, erythrocytes - 30 in the field (ranges 0 in the field - 3 in the field). Conclusion. This observation shows an urgent need for close interaction between nephrologists and rheumatologists in cases where an association of symptoms of both profiles presents, active collaboration with a patient, and the search for a personalized approach to treatment. It seems important to unite the efforts of the medical community in various countries to obtain more complete information about the features of the association of IgA nephropathy and SpA.